IMPLEMENTASI NILAI-NILAI PENDIDIKAN KARAKTER DALAM KITAB TA’LIMUL MUTA’ALLIM DALAM MENINGKATKAN PERILAKU RELEGIUS REMAJA MASJID WARINGINJAYA BEKASI - Madsari Edrian Annur; Ajat Rukajad; Yayat Heriana (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2022)
Finding new theories or new knowledge about the values ​​of character education in the Ta'limul muta'allim book. Research Methods In this study, a qualitative approach was used, namely that prioritizing data research based on the disclosures expressed by the respondents and the words collected in the form of words, pictures and not numbers. The author will also provide suggestions that are deemed necessary as a useful contribution in the world of Islamic education. The values ​​of character education in the book of Ta'limul Muta'allim by Sheikh al-Zarnuji which have been found by the author have 16 character values, namely: a. Love of science, the form of character education is 1) Learn and seek knowledge every day, 2) Learners use all their time to get used to contemplating the depths of knowledge, are never shy about taking lessons, and are not stingy to give lessons to others b. Love of peace, the form of character education is 1) Not studying the science of debate, 2) Keeping oneself from being hostile c. Democratic, the form of character education is 1) Always consult, 2) remind each other of lessons. For educators From the study of the values ​​of character education, it is expected to be a discourse for educators, both parents and teachers in fostering youth morals so that educational goals Islam to form human beings can be realized. In character building, an educator is expected not only to convey ethical or moral values, but must be able to instill these ethical values ​​in the souls of teenagers so that they can always color their daily behavior.